Comparing the APACHE II, SOFA, LOD, and SAPS II scores in patients who have developed a nosocomial infection - Haddadi, Ahmed; Ledmani, Mohamed; Gainier, Marc; Hubert, Hubert; De Micheaux, P Lafaye (Bangladesh Critical Care Journal, 2014)
Background: There have been numerous scores intended to evaluate the severity of patients condition upon admission and during their intensive care unit (ICU) stay. However, to our knowledge, no study has ever evaluated the predictive abilities of these scores among nosocomial patients during their ICU stay. The aim of our study is to compare the predictive performances of the Acute Physiology, and, Chronic Health Evaluation (APACHE II) score, Simplified Acute Physiologic Score (SAPS II), Logistic Organ Dysfunction (LOD), and Sequential Organ Failure Assessment (SOFA) scores among intensive care patients who have developed a nosocomial infection. Methods: The study is monocentric and retrospective. The APACHE II, SAPS II, LOD, and SOFA scores were reported from the third day of the patients hospital stay, preceding the diagnosis of the first nosocomial event up to the third post diagnosis day. Results: Out of 46 patients contracting at least one ICU-acquired infection, the multiple analyses indicated that on the day of diagnosis, the SOFA score is the most predictive (odds ratio [OR]: 12.3; 95% confidence interval [CI]: 2.3364.91). The second most predictive was the APACHE II score (OR: 8.29; 95% CI: 1.4348.14). The third and fourth most predictive were the LOD score (OR: 4.06; 95% CI: 0.8120.26) and the SAPS II score (OR: 2.26; 95% CI: 0.559.24), respectively. Conclusion: The analysis of the receiver operating characteristic areas under the curve of the reported scores in the present study showed that the best predictive performance is in favor of the SOFA score. DOI: http://dx.doi.org/10.3329/bccj.v2i1.19949 Bangladesh Crit Care J March 2014; 2 (1): 4-9